Beyond Redistribution : White Supremacy and Racial Justice. - Graham, Kevin M. (Lexington Books, 2012)
Kevin M. Graham argues that political philosophy cannot fully understand race-related injustice without shifting its focus away from distributive inequities between whites and nonwhites and toward white supremacy, the unfair power relationships that allow whites to dominate and oppress nonwhites. Graham's analysis of the racial politics of police violence and public education in Omaha, Nebraska, vividly illustrates why the pursuit of racial justice in the United States must move beyond redistribution.